Stock Market Reaction To The Announcement Of Sustainability Bond Issuance In Indonesia - Hasbi Azhari; Katiya Nahda (Cita konsultindo, 2026)
This study aims to analyze the stock market reaction to the announcement of sustainability bond issuance by companies listed on the Indonesia Stock Exchange. The announcement of sustainability bonds is considered important information as it reflects the company’s commitment to financing projects that generate environmental and social impacts. Therefore, this research seeks to examine whether such information is responded to by investors through changes in stock prices around the announcement date. This research employs a quantitative approach using the event study method. Market reactions are measured through Abnormal Return (AR), Average Abnormal Return (AAR), Cumulative Abnormal Return (CAR), and Cumulative Average Abnormal Return (CAAR). The observation period covers eleven trading days, from t−5 to t+5 surrounding the event date. The research sample is determined using purposive sampling based on the availability of stock price data and the absence of confounding events during the observation window. The data used are secondary data consisting of daily closing stock prices and the Composite Stock Price Index (IHSG) as a proxy for market returns. Statistical testing is conducted using a one-sample t-test to determine whether the abnormal returns differ significantly from zero. The findings indicate that, at the daily level, the Average Abnormal Return is not statistically significant, suggesting that the market does not react immediately to the announcement. However, at the individual cumulative level, the Cumulative Abnormal Return is significant, implying that investors adjust prices gradually after the information is released. Meanwhile, the Cumulative Average Abnormal Return is not significant, indicating that investor responses vary across firms and tend to offset one another. These results suggest that sustainability bond announcements contain relevant information for investors, yet their ability to generate a collective market reaction remains limited.